Disability in the Qur'an Manifestation of Repositioning from Exclusive to Inclusive - Niken Sylvia Puspitasari; Muhammad Zaidan Irfan; Muhamad Redho Al Faritzi (Islamic Religious Education Departement, 2024)
This research is motivated by the rise of ableism. This research aims to discover Disability in the Qur'an Manifestation of Repositioning from Exclusive to Inclusive. This research uses library research by making the library the primary source for obtaining data. This research uses a qualitative approach to examine the theme of disability in the Qur'an and how the sacred text can be understood in a modern context as an effort to reposition from exclusive to inclusive. The results show that the Qur'an has many words for disability, namely, a'ma/ umyun, akmah, bukmun, shummun, and a'raj. There are 38 verses spread across 26 surahs of the Quran. There are four verses in the entire Qur'an about a person that speaks directly about their attitude towards a disabled person or refers to a person with a physical disability. The Qur'an sees people with disabilities as having to be tolerant like ordinary people or behave equally towards others, especially those who are weak to discrimination, which is a manifestation of the repositioning of exclusive to inclusive.